Effects of Vinblastine and Vincristine on the function of chronic myeloid leukemic cells through expression of A20 and CYLD: Effects of Vinb and Vinc on leukemic cells - Hoang, Nguyen Huy; Huyen, Nguyen Thanh; Trang, Do Thi; Canh, Nguyen Xuan; Mao, Can Van; Sopjani, Mentor; Vuong, Nguyen Ba; Xuan, Nguyen Thi (Cellular and Molecular Biology, 2022)
Chronic myelogenous leukemia (CML) is characterised by the translocation of regions of the BCR and ABL genes, leading to the fusion gene BCR-ABL forming the Philadelphia (Ph) chromosome. Vinblastine (Vinb) and Vincristine (Vinc) are Vinca alkaloids and frequently used in combination chemotherapy in leukemias and lymphomas. Deubiquitinating enzyme (DUB) genes such as A20, Otubain 1 and CYLD are known as inhibitors of functional activation of immune cells mediated through the NF-κB/STAT pathway. Little is known about the regulatory role of Vinb/Vinc on the function of CML cells and the contribution of the DUBs to those effects. In the end, the gene expression profile was determined by quantitative RT-PCR, physiological properties of CML cells by flow cytometry and cytokine production by ELISA. As a result, inactivated expression of the DUBs A20, CYLD, Otubain 1 and Cezanne and enhanced activation of CD11b+ and CD4T cells were observed in CML patients. Importantly, Vinc enhanced the expression of A20 and CYLD and inhibited the proliferation and survival of CML (K562) cells. The effects were abolished in the presence of A20 siRNA, while cell proliferation only depended on the presence of CYLD. In conclusion, the up-regulation of A20 by Vinc could involve inhibitory effects on the proliferation and survival of K562 cells. The events might contribute to the anticancer effect of Vinc on A20-sensitive CML cells.